A Comparison of General Health and Mood State Profile in Bodybuilders with/withoutAnabolicSteroidConsumption - Meysam Shahhosseni; Hasan Gharayagh Zandi; Mojtaba Hasani Sangani (University of Tehran, 2016)
The aim ofthe current study wasto comparegeneral health and mood state profile in bodybuilders with/without anabolic steroid consumption. Thestatistical populationconsisted of all bodybuilders in Tehran city in 2015. 200 bodybuilders were selected from Tehran sport clubs with convenience sampling method. After excluding unauthorized questionnaire, 192 questionnaires were analyzed. The data were collected withGeneral-Health Questionnaire (GHQ), Mood State Profile Questionnaire and a researcher-made demographic questionnaire filled out by anabolic steroid users and non-usersin the sport clubs. Descriptive statistics and multivariate analysis of variance in SPSS20 were used to analyze the data. The results indicated a significant difference between anabolic steroid users and non-users in general health, its three subscales (physical, anxiety and social function dysmorphic), and two subscales of mood state profile (tension and anger). Accordingly, in addition to their physiological role in body, anabolic steroid has devastating effects on athletes' general health and mood.